The Use of Film Stories to Improve Students’ Ability in Writing Narrative Text - Rini Anggriani; Amirullah Abduh; Amra Ariyani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
This study aimed to discover whether the use of film stories could improve students’ ability in writing narrative text. The method of the research was pre-experimental with one group pretest and posttest design. The population of the study was 11th Grade students of Senior High School MA DDI Kanang, West Sulawesi in the 2021/2022 academic year. Twenty-five (25) students were selected as samples of the study using a random sampling technique. The instrument of this research was a writing test which was administered as a pretest and posttest. Descriptive statistics were used to analyze the data. The results of the data analysis showed that the posttest mean score was 83.84. This was greater than the pretest mean score that was 68.96. Furthermore, the significant value of this research (0.000) was smaller than the alpha level (0.05). this means that H0 is rejected and H1 is accepted. Therefore, it can be concluded that Film stories could be used as media in improving the students’ ability in writing a narrative text of 11th Grades of MA DDI Kanang.